Pension reform, retirement and life-cycle unemployment - Christian Jaag; Christian Keuschnigg; Mirela Keuschnigg (Center for Economic Studies and ifo Institute (CESifo), 2007)
The labor market effects of pension reform stem from retirement behavior and from job search and hours worked of prime age workers. This paper investigates the impact of four often proposed policy measures for sustainable pensions: strengthening the tax benefit link, moving from wage to price indexation of benefits, lengthening calculation periods, and introducing more actuarial fairness in pension assessment. We provide some analytical results and use a computational model to demonstrate the economic and welfare impact of recent pension reform in Austria.
Keywords: D58; D91; H55; J26; J64; 330; pension reform; retirement; job search; life-cycle unemployment; Rentenreform; Altersgrenze; Arbeitslosigkeit; Erwerbstätigkeit; Overlapping Generations; Umlageverfahren; Österreich; Simulation; Theorie